Bible Studies in the Life of Paul, Historical and Constructive - Sell, Henry T. (Henry Thorne), 1854-1928 (Salt Lake City, UT : Project Gutenberg, 2010)
"Bible Studies in the Life of Paul, Historical and Constructive" by Henry T. Sell is a historical and religious text written in the early 20th century. The work delves into the life and contributions of the Apostle Paul, exploring his mission to spread Christianity to the Gentile world, as well as his formative experiences, travels, and the theological insights he developed along the way. This book serves as an educational resource designed for Bible study groups, Sunday schools, and personal study, underlining Paul's significance in the early Christian church. At the start of the book, the author expresses the intent to provide a structured analysis of Paul's life, detailing his background, conversion, and missionary journeys. The preface emphasizes how Paul was chosen by Christ to further the gospel amidst great opposition. In the opening chapter, Sell outlines Paul's early life$1 (Bincluding his education, upbringing, and the socio-political environment of the time$1 (Bestablishing a foundation for understanding the Apostle's later actions. It sets the stage for a deeper exploration of Paul's conversion experience and the implications of his missionary efforts, which would follow in subsequent studies. (This is an automatically generated summary.)s
Release date is 2010-02-22
Produced by Al Haines
Keywords: Paul, the Apostle, Saint